Communication skills for the health care professional context, concepts, practice, and evidence - Van Servellen, Gwen 1942- (Burlington, MA Jones & Bartlett Learning, 2020)
"Communication Skills for the Health Care Professional addresses the connection between communication practices and quality patient care outcomes. It provides future and practicing patient caregivers in all specialties and services with basic communication knowledge and skills and is an invaluable resource for those in administrative functions as well. The Third Edition is a thorough revision that features many new chapters while also combining other chapters for a text that can be used in a single semester course. Features: Provides a psychosocial and physiologic contextual background for understanding sensual development and verbal and nonverbal expression. Teaches communication skills one at a time allowing for contiguous mastery over a set of therapeutic interventions. Includes an extensive glossary of terms and list of references including websites and resources available to enhance student learning."--Provided by publisher.
Part I. The Context for Health Care Communications in an Evolving Health Care System -- Part II. Foundations for Understanding Communications in Health Care -- Part III. Critical Competencies in Therapeutic Communications -- Part IV. Communications to Ensure Comprehensive and Continuous Patient-Centered Care under Challenging Circumstances -- Part V. Beyond Patient-Provider Encounters: Managing Communications Within and Across Relevant Constituencies -- Part VI. Ethics and Communications in Health Care -- Part VII. Transforming Health Care through Changing Patient Behaviors and Systems of Care -- Part VIII. Evidence Supports the Importance of Effective Communications.
Includes bibliographical references and index.
Keywords: Allied health personnel and patient; Interpersonal communication; Communication in medicine